A novel role of angiotensin II in epidermal cell lineage determination: Angiotensin II promotes the differentiation of mesenchymal stem cells into keratinocytes through the p38 MAPK, JNK and JAK2 signalling pathways. Issue 1 (15th January 2019) - Jiang, Xiao; Wu, Fan; Xu, Yuan; Yan, Jian‐Xin; Wu, Yin‐Di; Li, Sheng‐Hong; Liao, Xuan; Liang, Jun‐Xian; Li, Ze‐Hua; Liu, Hong‐Wei
Abstract: Background: Recent evidence suggests that angiotensin II (Ang II) plays a role in cutaneous wound healing. Mesenchymal stem cells (MSCs) are known as a rich source of cells that re‐establish healed skin. However, the potential impact of Ang II on MSC differentiation into keratinocytes is still unknown. Objective: The present study was conducted to explore the effect of Ang II on the differentiation of bone marrow‐derived MSCs (BM‐MSCs) into keratinocytes. Methods: Bone marrow‐derived MSCs were isolated from rat bone marrow and cultured. The expression of Ang II type 1 (AT1 ) and type 2 (AT2 ) receptors was examined by immunofluorescence staining. The differentiation of BM‐MSCs into keratinocytes was investigated by flow cytometry or/and histological observation. Results: The BM‐MSCs constitutively expressed both AT1 and AT2 receptors. The differentiation of BM‐MSCs into keratinocytes was successfully induced. Interestingly, incubation of BM‐MSCs with Ang II further promoted the differentiation of BM‐MSCs into keratinocyte, which was abolished by pretreament with losartan, an AT1 receptor antagonist, but not by PD123319, an AT2 receptor antagonist. Moreover, the p38 mitogen‐activated protein kinase (MAPK) inhibitor SB203580, the c‐Jun N‐terminal kinase (JNK) inhibitor SP600125 and the Janus‐activated kinase (JAK)2 inhibitor AG490 suppressed Ang II‐induced differentiation of BM‐MSCs into keratinocytes. The phosphoinositide‐3 kinase (PI3K) inhibitor wortmannin and MEK1/2 inhibitor U0126 had no effect on BM‐MSC differentiation into keratinocytes. Conclusions: Our data demonstrated for the first time that Ang II plays a promotive role in the differentiation of BM‐MSC into keratinocytes through the AT1 receptor, and that the p38 MAPK, JNK and JAK2 signalling pathways are involved in this process.